IDENTITY AND REPRESENTATION IN MOLDOVAN ENTERTAINMENT MEDIA SPACE - Sanina, Tatiana (Wake Forest University, 2021)
This study aims to identify whether entertainment media broadcast in Republic Moldova, which struggles with its identity crisis, contains frames that represent belonging to a particular national identity. Secondly, the study is preoccupied with the cinematic representations that can influence the perception of group identity. While this study focuses on group identity as a nation, it is important to understand the mechanisms of identification at the individual or micro-level, as those divisions position one in relation to a group. In the context of the multitude of cultural identities and several historic shifts on the territory of Moldova, this study adopts Tajfel’s social identity framework to explain the identification with a particular in-group and how this identification is represented in fictional media. Eight codes based on the NATID scale were applied to analyze the sample data consisting of the seven most viewed films on Moldovan television in 2019. All the films in this study were produced in Russia from 2013 to 2018. The results demonstrated the presence of identity frames under the selected codes that depict national heritage, cultural homogeneity, beliefs system, and ethnocentrism characteristic to Russian culture, which is patriarchal, based on conservative values and beliefs. While Moldovans experience the identity of “becoming”, being subject to constant transformations at the intersection of history, culture, and power, media plays a role of crucial importance for the consolidation of perceptions and possibilities, and as a result, it helps shape social and political attitudes of the viewers.